2019
DOI: 10.26434/chemrxiv.8298776.v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Analytic First-Order Derivatives of Partially Contracted N-Electron Valence State Second-Order Perturbation Theory (PC-NEVPT2)

Abstract: A balanced treatment of dynamic and static electron correlation is important in computational chemistry, and multireference perturbation theory (MRPT) is able to do this at a reasonable computational cost. In this paper, analytic first-order derivatives, speci cally gradients and dipole moments, are developed for a particular MRPT method, state-specific partially contracted n-electron valence state second-order perturbation theory (PC-NEVPT2). Only one linear equation needs to be solved for the derivative cal… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 70 publications
(123 reference statements)
0
7
0
Order By: Relevance
“…which are roughly equivalent to the "orbital Lagrangian" and the "configuration Lagrangian," respectively, in the author's previous studies. 18,40 Once all the Lagrangian multipliers are determined by solving the Z-vector equation, as in the case of the state-averaged RASSCF [Eq. (11) but where L RASSCF is replaced with L RASPT2 ], the derivative of the RASPT2 energy can be evaluated by…”
Section: B First-order Derivativesmentioning
confidence: 99%
See 2 more Smart Citations
“…which are roughly equivalent to the "orbital Lagrangian" and the "configuration Lagrangian," respectively, in the author's previous studies. 18,40 Once all the Lagrangian multipliers are determined by solving the Z-vector equation, as in the case of the state-averaged RASSCF [Eq. (11) but where L RASSCF is replaced with L RASPT2 ], the derivative of the RASPT2 energy can be evaluated by…”
Section: B First-order Derivativesmentioning
confidence: 99%
“…Recent efforts to develop analytic derivatives of MRPTs 15 have made it possible to efficiently compute properties. Earlier studies reported such implementations in MOLPRO, 16 BAGEL, 17 GAMESS-US, 18 and TeraChem 19 for different MRPT methods. However, the size of the active space in these past works was rather limited.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…which are roughly equivalent to the "orbital Lagrangian" and the "configuration Lagrangian," respectively, in the author's previous studies. 18,40 Once all the Lagrangian multipliers are determined by solving the Z-vector equation, as in the case of the state-averaged RASSCF [Eq. (11) but where L RASSCF is replaced with L RASPT2 ], the derivative of the RASPT2 energy can be evaluated by…”
Section: B First-order Derivativesmentioning
confidence: 99%
“…The most well-known MRPT is probably the CAS second-order PT (CASPT2) method, [8][9][10] but many other versions exist, such as (extended) 11 multiconfiguration quasi-degenerate PT2 [(X)MCQDPT2], 12 n-electron valence state PT2 (NEVPT2), [13][14][15] generalized Van Vleck PT2 (GVVPT2), 16 retaining the excitation degree PT, 17 unitary group adapted state-specific MRPT, 18 and driven similarity renormalization group state-averaged MRPT (SA-DSRG-MRPT2). 19 There is no doubt that analytic derivatives are most convenient to locate minimum energy structures, such that analytic gradient theories and programs have been developed for a variety of MRPTs, namely CASPT2, [20][21][22][23] GVVPT2, 24 NEVPT2, 25,26 (X)MCQDPT2, 27 and (SA-)DSRG-MRPT2. 28,29 Another type of multiconfigurational approach, such as multiconfiguration pair-density functional theory (MC-PDFT), 30 has analytic derivative theories 31 as well.…”
Section: Introductionmentioning
confidence: 99%